Avaliação do ciclo de vida de um laminado sintético espalmado de PVC para produção de palmilhas - Dutra, Felipe Juliano (Universidade Federal de São Carlos, 2024)
Brazil is currently the fifth largest footwear producer in the world, accounting for 3.9% of global production. In Brazil, there is a tendency to increase the use of synthetic laminates in footwear, mainly due to the variety of colors, prints, thicknesses, and applications with emphasis on PU (polyurethane) and PVC (polyvinyl chloride) laminates. Although PVC is an important alternative in the manufacture of footwear, its use is still questioned from an environmental point of view, mainly due to the emissions throughout the production process, such as dioxins. Therefore, the objective of this work is to present the main environmental hotspots of a synthetic PVC laminate used to make insoles, by carrying out an LCA from cradle to gate, based on a case study. Four impact categories were assessed, based on literature: abiotic depletion, eutrophication, human toxicity, and global warming. The results indicate that the main environmental hotspots occur upstream of the laminate production process for three of the four categories analyzed: production of plasticizer (non-phthalic) for the abiotic depletion and eutrophication categories, and production of emulsion PVC resin (E) for the human toxicity category. The production process of the assessed laminate directly contributes to the potential impacts observed for the global warming category. The possible actions to reduce potential environmental impacts assessed in this study are: the use of vegetable plasticizers and the use of energy from renewable sources, among which, the replacement of plasticizer (non-phthalic) by soybean oil proved to be the most advantageous scenario in the environmental point of view.
Life cycle assessment of a PVC spread coating synthetic laminate to produce insoles
Keywords: ACV; PVC; Cadeia calçadista; Impactos ambientais potenciais; LCA; Footwear chain; Potential environmental impacts; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO